2018
DOI: 10.1080/21691401.2018.1478844
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab (anti-CD20)-modified AZD-2014-encapsulated nanoparticles killing of B lymphoma cells

Abstract: The mTOR signal pathway is often highly activated in B-cell non-Hodgkin's lymphoma (NHL) and promotes cancer progression and chemo-resistance. Therefore, the pathways of mTOR are an important target for drug development in this disease. In the current study, we developed a rituximab (anti-CD20)-modified mTOR inhibitor, AZD-2014, loaded into nanoparticles (Ab-NPs-AZD-2014) for trial of its anti-NHL effect. In a cultured NHL cell line, Ab-NPs-AZD-2014 inhibited cancer cell growth, induced cell apoptosis, and blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The targeted therapies against CD20 are not limited to antibodies. Recently, CD20 found to be an potential receptor in nanomedicine [ 17 ] and cancer immunotherapy [ 18 ]. For instance, there are some CAR-T and NK cells under investigation for CD20 + lymphoma (7, 8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The targeted therapies against CD20 are not limited to antibodies. Recently, CD20 found to be an potential receptor in nanomedicine [ 17 ] and cancer immunotherapy [ 18 ]. For instance, there are some CAR-T and NK cells under investigation for CD20 + lymphoma (7, 8).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, mAb used to be generated in mice, such as anti-CD3 Muromomab. However, murine-derived mAbs raised human anti-mouse antibody (HAMA) responses in some patients [ 17 ]. To address this issue, mAbs were engineered to incorporate more human sequences to alleviate side effects, which resulted in Chimeric and Humanized mAb.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterial loading of an mTOR inhibitor inhibited the expression of 4E-BP1 in B lymphoma cells. 37 However, there is no satisfactory research on nanomaterials without contents assessing changes in 4E-BP1 levels. 4E-BP1 is a downstream effector of mTOR, 38 and its expression is higher in PCa tissue than in normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al . reported a rituximab (anti-CD20)-modified AZD-2014 encapsulated nanoparticle for killing B lymphoma cells [ 220 ]. Torino et al .…”
Section: Nanomedicine Strategies Against Hmsmentioning
confidence: 99%
“…Regarding other targets, Nevala et al reported an CD20 antibody-modified paclitaxelloaded nanoparticle for the treatment of CD20 + B cell lymphoma [219]. Tang et al reported a rituximab (anti-CD20)-modified AZD-2014 encapsulated nanoparticle for killing B lymphoma cells [220]. Torino et al reported a BCR-targeted multimodal imaging-engineered nanoparticle for the therapeutic and diagnosis of B cell lymphoma [221].…”
Section: Targeting Cancer Cellsmentioning
confidence: 99%